Towards good corporate governance: an analysis of corporate governance reforms in Uganda - Tumuheki, Justine (Department of Commercial Law, 2014)
The recent onslaught of corporate scandals has compelled the world to acknowledge the profound impact of corporate governance practices on the global economy. Corporate governance has become important for the survival of companies and indeed of national economies in the increasingly global economy. Corporate governance is of particular concern in developing economies, where the infusion of international investor capital and foreign aid is essential to economic stability and growth. For transition economies, such as Uganda's, which are faced with the challenge of restructuring for greater efficiency and creating a foreign investment-friendly environment, good corporate governance is crucial for success. This research highlights corporate governance initiatives in Uganda, focusing on the proposed corporate governance reforms. An analysis of the major corporate governance reforms is done including; statutory reforms, development of codes of conduct and best practice and institutional reforms. The evolution of Uganda's corporate structure and the forces driving corporate governance reform is examined. It is noted that corporations in Uganda cannot shield themselves from the global movement that is shaping standard principles governing corporations. Therefore the global principles of corporate governance are examined concerning how they can serve as models for enhancing corporate governance standards in Uganda. The analysis is based on the need to bring Uganda's corporate governance reforms in line with internationally accepted standards but considering the best interests of Uganda and its citizens.